Application of creative ideation practices using the example of school storage system design - Rassadina Svetlana P.; Lukhmanova Maria E. (Архитектон)
The article presents the results of the practical application of ideation methods in the search for design solutions for the storage of school supplies, inventory and personal belongings of students. Current ideation techniques used in design are analyzed. A series of ideas found using methods such as Mental Map, Synectics, SCAMPER, Bionics, Focal Object Method, and Morphological Box are graphically presented. The progress of work on the design project to create a universal modular school storage system is illustrated as a continuation of a previously conducted analysis of modern school spatial environments and storage systems. Various options of storage modules assembly in a school environment are presented. The work is interesting from both design and methodological points of view as it allows one to identify key elements in creativity and creative thinking and provides a structured approach to the research and development of these aspects.